Polanyi in the United States: Peter Drucker, Karl Polanyi, and the Midcentury Critique of Economic Society - Immerwahr, Daniel (Journal of the History of Ideas, 2009)
Abstract:This essay explores the connections between Karl Polanyi's The Great Transformation (1944) and midcentury social theory in the United States. It argues that Polanyi shared with his U.S. colleagues a critique of market society. In particular, Polanyi's work bears close resemblance to the early thought of management theorist Peter Drucker, with whom Polanyi lived while writing his celebrated book. By comparing Polanyi to his contemporaries who advanced similar ideas, one gains a clearer sense of the particularities of Polanyi's project and of the fairly widespread movement in the United States to reject economistic thinking.
Keywords: DRUCKER, Peter; history; social theory

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
Keywords: biography; essence of fascism

Hititlerde Devlet Gelirleri, Depolama ve Yeniden Dağıtım - Reyhan, Esma (The Revenues of Hittite State, Storage and Redistribution., 2009)
The economic system of Hittite Kingdom shows parallelism with a description of Polanyi about redistribution system, as "Tributes firstly flow to the capital of an emperor, and then from there to the provinces". This system completely depended upon the social hierarchy. Tributes firstly flow to the capital of an emperor, and then from there to the provinces. This essay examines the tax collection system of the Hittite Empire, especially the aspect of redistribution of the taxes from the capital to the provinces. As the taxes flow firstly into Hattuşa and later to the provinces, we are trying to draw the conceptional frame of the "redistribution in centralized system". This will also make it possible to consider the management structure of the Hittite Empire as well. (English)
Keywords: Hattuşa/Boğazköy; Hattuša/Boğazköy; Hitit Devleti; Hitit Ekonomik Sistemi; Hitit Kanunları; Hitit Ritüel Metinleri; Hitit Çiviyazılı Tabletler; Hittite Cuneiform Tablets; Hittite Economic System; Hittite Laws; Hittite Ritual Texts; Hittite State; Hittites; capital cities; dominance (psychology); kings & rulers; storage; tax administration & procedure; tax collection; tax penalties; warehouses

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Karl Polanyi : une voix du siècle passé, Abstract - Cangiani, Michele (Revue du MAUSS, 2009)
RésuméSituer Karl Polanyi dans son temps et par rapport aux grandes théories sociales du passé, y compris celle de Marx, nous permet de mieux comprendre les problèmes du temps présent. C’est de ce point de vue que l’article cherche à mettre brièvement en relief quelques aspects de la contribution de Polanyi à la connaissance historique, à la critique de la science économique et à la théorie politique., To consider Karl Polanyi’s thought in relation to his time and to great social theories of the past, Marx’s theory to begin with, can improve our understanding of problems of current times. This is the starting point of this article’s attempt to synthetically focus some aspects of Polanyi’s contribution to historical knowledge and political theory, and of his critique of economics.
Keywords: political theory